2012
DOI: 10.4021/cr95w
|View full text |Cite
|
Sign up to set email alerts
|

Smoking was a Possible Negative Predictor of Incident Hypertension After a Five-Year Follow-up Among a General Japanese Population

Abstract: BackgroundsThe association between cigarette smoking and hypertension is controversial. The aim of this study is to investigate the association between smoking and incident hypertension.MethodsThis is a post-hoc five-year follow-up study in a general Japanese population. Logistic regressions were performed using incident hypertension as an outcome and smoking status as an independent predictor adjusting for sex, age, body mass index (BMI), total cholesterol, high-density lipoprotein (HDL) cholesterol, triglyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Smoking has been largely recognised as an important risk factor of hypertension. It is associated with phenomena involved in hypertension’s pathogenesis, such as endothelial dysfunction 40 , atherosclerotic plaque formation 41 or arterial stiffness 42 and it showed to have a role in the development of hypertension in epidemiological studies 15,16,43,44 . However, our findings are not isolated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking has been largely recognised as an important risk factor of hypertension. It is associated with phenomena involved in hypertension’s pathogenesis, such as endothelial dysfunction 40 , atherosclerotic plaque formation 41 or arterial stiffness 42 and it showed to have a role in the development of hypertension in epidemiological studies 15,16,43,44 . However, our findings are not isolated.…”
Section: Discussionmentioning
confidence: 99%
“…So far the largest body of literature analysed MLFs separately, and information about how they are combined in the population and how such combinations impact risk are scarce, as well as information about clusters of association and mutual interactions. We identified six MLFs with sufficient evidence of a causal co-responsibility regarding the occurrence of hypertension: general and abdominal obesity 10–12 , excessive use of alcohol 13,14 , smoking 15,16 , lack of physical activity 17 and low adherence to the DASH (Dietary Approaches to Stop Hypertension) diet 18,19 . Therefore, this study aimed to provide information about the prevalence and risk association of the MLFs combinations observed in a large adult German cohort, with insights about clustering and interactions of MLFs.…”
Section: Introductionmentioning
confidence: 99%
“…22 Smokers have Open access a higher risk of hypertension, with 16.9% for men and 27.6% for women compared with non-smokers. 23 It has also been reported that dual users of CC and EC have a higher prevalence of metabolic syndrome than exclusive CC smokers. 24 Therefore, the results of this study can be thought of as reflecting a larger number of smokers in patients with hypertension and hyperlipidaemia because it is a cross-sectional study.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, diverse evidence suggests an inverse relationship between these factors. Kaneko et al 47 , in a recent study of 1297 Japanese individuals without any history of high blood pressure, showed that cigarette smoking appeared to be a “protective” factor against blood pressure elevation. Onat et al 48 observed a similar pattern in a Turkish population.…”
Section: Discussionmentioning
confidence: 99%